Eroded porous-media aquifer controlled hydrovolcanic centers in the South Lake Balaton region, Hungary: The Boglar volcano - Nemeth K; Martin U; Philippe M (Akadmiai Kiad, 1999)
The volcanic centers next to Balatonboglar township represent 3.5 Ma old products of post-extensional alkaline basaltic volcanism in the Pannonian Basin (eastern Central Europe). They are small, eroded volcanic centers located on the southern shore of Lake Balaton and genetically related to the Bakony-Balaton Highland Volcanic Field eruptive centers. The relatively small area (500 m x 500 m) contains at least 2 eruptive centers, which are probably related to each other and have built up a complex volcano, called the Boglar Volcano. The volcanic rocks overlie the older Pannonian clastic sedimentary sequence and represent the topographic highs in this area. The areas of lower elevation around the eruptive centers are covered by Pleistocene to Holocene swamp, lake and river clastic sediments, which strongly suggest intense erosion during the last few million years. All volcanic rocks around Balatonboglar are volcaniclastic. There is no evidence of lava flow occurrence. The volcaniclastic sediments have been divided into two lithofacies associations. The largest amount of volcaniclastic rocks is located in the center of the local hills and has been interpreted as a phreatomagmatic crater fill lapilli tuff. They contain large amphibole megacrysts and small olivine crystals. The second lithofacies association is interpreted as lahar deposits. This sequence contains an unusually large amount of fossil tree trunks, which are identified as Abies species. Within a small area in the western hills small outcrops show evidence of maar-lake clastic sediment occurrence. On the hilltops debris shows intimate interaction processes between clastic sediments and basaltic melt. We interpret this to mean that the eruptive centers of Boglar Volcano were formed under subaerial conditions, with explosions fueled by intensive interaction between water-saturated Pannonian sand and uprising basaltic magma.
Keywords: Phreatomagmatism; Hydrovolcanism; Maar; Diatreme; Strombolian; Pannonian Basin; Bakony-Balaton Highland Volcanic Field